Improvement of The Gradation of Basic Soil Grains With The Addition of Cement and Clay Soil Against Cbr Values (Hukurila-Seri Ring Road Case Study) - SM. Andika Para; Abraham Kalalimbong; Mansye Ronal Ayal (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The condition of the subgrade soil on the Hukurila-Seri Ring Road section, Ambon City has the potential to experience a decrease in carrying capacity due to the abandonment of construction projects. To overcome these problems, efforts are made to improve the soil using the stabilization method using additional materials in the form of cement and clay soil. This study aims to determine the classification of soil at the location, as well as evaluate the effect of the addition of cement and clay soil on soil grain gradation and CBR (California Bearing Ratio) value. The test was carried out in the laboratory using native soil taken from the research site, then mixed with variations of cement (4%, 7%, and 10%) as well as a combination of optimum cement + clay soil (2%, 9%, and 24%). The results of the study showed that the addition of cement significantly increased the CBR value of the soil. The optimum mixture is obtained at the 10% cement variation which provides the highest increase in CBR value.